Estudio sobre la calidad de servicio de la Cooperativa de Transportes Unión Cariamanga - Tamay Calva, Genesis Deyaneira (2022)
Nowadays, offering high-quality service is of vital importance within an organization since it is the only guarantee of being competitive and staying in the market. For that reason, this investigation is framed to determine the quality level of the services provided in “Cooperativa de Transportes Unión Cariamanga”. Thus, the research was carried out by using a descriptive and quantitative approach, an inductive and deductive method, and applying observation, surveying, and bibliographic sources as the main techniques. The sample consisted of 383 customers that were randomly chosen from 749,163, which was the population. A survey of 22 questions, which were divided according to the five dimensions established by the SERVPERF model, was applied to the customers. It is concluded that the clients of “Cooperativa de Transportes Unión Cariamanga” are satisfied with the service provided because the results showed that the dimensions with the highest degree of satisfaction were reliability, empathy, and trustworthiness. On the other hand, the dimensions that obtained the lowest degree of satisfaction were responsiveness and tangibility. This is corroborated by the satisfaction index of 5.47 points on a scale of 1 to 7 established by the SERVPERF model. This allowed the identification of short and long-term opportunities for improvement to mark the difference in the scale.